VBScript in a nutshell - Lomax, Paul (In a nutshell (O'Reilly & Associates), 2003)
"Lightweight yet powerful, VBScript from Microsoft is used in four main areas: server-side web applications using Active Server Pages (ASP), client-side web scripts using Internet Explorer, code behind Outlook forms, and the automation of repetitive tasks using Windows Script Host (WSH), VBScript in a Nutshell, Second Edition, delivers current and complete documentation for programmers and system administrators who want to develop effective scripts in all four areas." "Completely updated for VBScript 5.6, WSH 5.6, and ASP 3.0, VBScript in a Nutshell, Second Edition includes introductory chapters that will help you keep current with the significant changes since the first edition was published. A new chapter introduces the Windows Script Component for creating binary COM components, and an appendix documents the Script Encoder. The main part of the book is a comprehensive alphabetical reference to the VBScript language and the Scripting Runtime Library."--Jacket